Naturaleza y espacio : la arquitectura de Harold Martínez Espinal - Iglesias García, Verónica; Ortíz Moya, Hilda Graciela (Colección Artes y humanidades (Universidad del Valle), 2016)
The work of the Colombian architect Harold Martínez Espinal, shows a way to purposeful way of thinking the architecture in the suburbs. This book makes a journey from his first works in the 1960's and 1970's, determined by the influence of modern architecture, until the beginning of the second millennium where his thought continues.